Physicochemical characterization of the thermo‐induced self‐assembly of thermo‐responsive PDMAEMA‐b‐PDEGMA copolymers. Issue 7 (1st February 2015) - Wagner, Michael; Pietsch, Christian; Kerth, Andreas; Traeger, Anja; Schubert, Ulrich S.
ABSTRACT Diblock copolymers of poly[2‐(dimethylamino)ethyl methacrylate]‐block‐poly[di(ethylene glycol) methyl ether methacrylate], PDMAEMA‐b‐PDEGMA, were synthesized by reversible addition–fragmentation chain transfer polymerization. The block ratio was varied to study the influence on the lower critical solution temperature and the corresponding phase transition in water. Therefore, turbidimetry, differential scanning calorimetry (DSC), dynamic light scattering (DLS), and laser Doppler velocimetry were applied. Additionally, asymmetric flow field‐flow fractionation (AF4) coupled to DLS and multiangle laser light scattering (MALLS) was established as an alternative route to characterize these systems in terms of molar mass of the polymer chain and size of the colloids after the phase transition. It was found that AF4–MALLS allowed accurate determination of molar masses in the studied range. Nevertheless, some limitations were observed, which were critically discussed. The cloud point and phase transition of all materials, as revealed by turbidimetry, could be confirmed by DSC. For block copolymers with block ratios in the range of 50:50, a thermo‐induced self‐assembly into micellar and vesicular structures with hydrodynamic radii (Rh) of around 25 nm was observed upon heating. At higher temperatures, a reordering of the self‐assembled structures could be detected. The thermo‐responsive behavior was further investigated in dependence of pH value and ionic strength. Variation of the pH value mainly influences the solubility of the PDMAEMA segment, where a decrease of the pH value increases the transition temperature. An increase of ionic strength leads to a reduction of the cloud point due to the screening of electrostatic interactions. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 924–935